Case report: Scald burn to the scalp complicated by fungal kerion - Theresa Nguyen; Krist Y.H. Ewe; Fiona Wood; Suzanne Rea; Asha C. Bowen (Elsevier, 2020)
Fungal kerion is a hypersensitivity reaction to a scalp dermatophyte which gains access to the hair shaft following physical trauma. However, precipitating injuries are rarely reported. We report the case of a 4-year-old girl who presented with non-healing scalp lesions following a deep dermal forehead scald caused by hot water. The third degree burn was epithelialized with two autologous split skin grafts from a donor thigh site. The grafts were complicated by early bacterial infection treated with intravenous antibiotics. The child returned to her remote community and was lost to follow up. Three months later, fungal kerion at the same site as the burn was clinically diagnosed and confirmed with culture of Trichophyton tonsurans from plucked hair samples. Her condition improved after treatment with oral terbinafine and co-trimoxazole (for suspected bacterial co-infection). Clinical recognition of fungal kerion following a deep burn injury as a trauma mechanism is presented to facilitate early recognition in other children with similar risk factors.